2020
DOI: 10.1186/s41181-020-00109-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved non-invasive positron emission tomographic imaging of chemotherapy-induced tumor cell death using Zirconium-89-labeled APOMAB®

Abstract: Purpose The chimeric monoclonal antibody (mAb) chDAB4 (APOMAB®) targets the Lupus associated (La)/Sjögren Syndrome-B (SSB) antigen, which is over-expressed in tumors but only becomes available for antibody binding in dead tumor cells. Hence, chDAB4 may be used as a novel theranostic tool to distinguish between responders and nonresponders early after chemotherapy. Here, we aimed to ascertain which positron emitter, Zirconium-89 ([89Zr]ZrIV) or Iodine-124 ([124I]I), was best suited to label chDAB4 for post-chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(48 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…For example, Donnelly et al compared their novel chelator, DFO-Sq, which is a squaramide ester derivative of DFO-pPhe-NCS, to DFO-pPhe-NCS using the HER2-targeting antibody, trastuzumab, and showed improved radiolabeling efficiency and PET imaging characteristics resulting from use of the DFO-Sq chelator [58]. Similarly, in a study of [ 89 Zr]Zr-chDAB4, we found that DFO-Sq as a chelator led to better in vitro and in vivo stability and PET imaging quality than DFO-pPhe-NCS [41]. Another recent study confirmed the very good shelf stability and high chemical purity of a [ 89 Zr]Zr-labeled immunoconjugate employing the DFO-Sq chelator [59].…”
Section: Discussionmentioning
confidence: 61%
“…For example, Donnelly et al compared their novel chelator, DFO-Sq, which is a squaramide ester derivative of DFO-pPhe-NCS, to DFO-pPhe-NCS using the HER2-targeting antibody, trastuzumab, and showed improved radiolabeling efficiency and PET imaging characteristics resulting from use of the DFO-Sq chelator [58]. Similarly, in a study of [ 89 Zr]Zr-chDAB4, we found that DFO-Sq as a chelator led to better in vitro and in vivo stability and PET imaging quality than DFO-pPhe-NCS [41]. Another recent study confirmed the very good shelf stability and high chemical purity of a [ 89 Zr]Zr-labeled immunoconjugate employing the DFO-Sq chelator [59].…”
Section: Discussionmentioning
confidence: 61%
“…The construction of [ 89 Zr]Zr‐DFO‐RAM began with the conjugation of DFO to RAM and resulted in an immunoconjugate of average ratio 1.2:1 (DFO:RAM), which was an acceptable result compared with the previously published conjugation efficacy (1.3 DFO per antibody) in 89 Zr labelling 24 . [ 89 Zr]Zr‐DFO‐RAM radiochemical purity was over 95%, a level that enabled in vitro and in vivo experiments with no need of further purification.…”
Section: Discussionmentioning
confidence: 99%
“…The presented study focused on the application of in 89 Zr labelling. 24 [ 89 Zr]Zr-DFO-RAM radiochemical purity was over 95%, a level that enabled in vitro and in vivo experiments with no need of further purification.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, radionuclides such as gallium-68 (t 1/2 = 67.7 min) are preferred for antibody fragments and mimetics with a very short serum half-life such as nanobodies or affibodies (see Table 1). Although 89 Zr, 64 Cu, and 68 Ga are the most commonly used radiometals for radiolabeling of antibodies, none of them are perfect, triggering research on other emerging radiometals such as manganese-52, yttrium-86, gallium-66, and scandium-44. Moreover, recent advances in [ 18 F]AlF radiochemistry expand the options for radiolabeling of antibodies with 18 F. 18 F is by far the most commonly used PET radionuclide thanks to its short half-life (110 min), its ideal physical properties as extensively shown in small molecule imaging, and its increasing availability.…”
Section: ■ Antibodies and Immuno-petmentioning
confidence: 99%
“…Radiometals and chelators have extensively been evaluated to come to the most ideal radiometal−chelator pair for each type of antibody derivative. Although PET imaging of antibodies is a relatively recent tool, applications with 89 Zr, 64 Cu, and 68 Ga have greatly increased in recent years, especially in the clinical setting, while other less common radionuclides such as 52 Mn, 86 Y, 66 Ga, and 44 Sc, but also 18 F as in [ 18 F]AlF are emerging promising candidates for the radiolabeling of antibodies. This review presents a state of the art overview of the practical aspects of radiolabeling of antibodies, ranging from fast kinetic affibodies and nanobodies to slow kinetic intact mAbs.…”
mentioning
confidence: 99%